معايري اختيار النصوص األدبية العربية يف املرحلة الثانوية الدينية العاليةالماليزية: دراسة تقوميية = Evaluating the standards of choosing Arabic literary texts on the Malaysian Secondary Religious High School Level = Analisis beberapa kriteria pemilihan teks sastera Arab di Peringkat Sijil Tinggi Agama Malaysia (STAM) - Ismail, Yasir; Salleh, Radziah (Department of Arabic Language and Literature, IIUM, 2014)
The subject of literature is significant on the secondary level to raise the language competency level of students and to cultivate their interest in literary sensibility. The literary subject in the syllabus of Malaysian high school religious certificate is compulsory. Unfortunately, there are no clear tenets for the selection of the literary texts in the subject. Consequently, the perception among students is that the texts are beyond comprehension and learning. It is possible to claim that this might be one of the explanations to the decline in the competency in Arabic among those students. The students do not feel encouraged to read continuously the texts since they are difficult, ambiguous and complicated. This paper attempts to point out the shortcomings in the selection of the structure and content of those texts. Structurally, the study focuses on the selection aspect of the words, phrases and size of the text. As for the content, the aspects of culture, psychology and education of the texts are the focus of discussion. The paper will recommend a number of alternative Arabic texts that would suit the level of those students. Finally, the paper concludes a number of recommendations for the parties involved in textbook syllabus to take into consideration to select properly texts for this purpose.